Alcohol intake and the risk of coronary heart disease in the Spanish EPIC cohort study. Issue 2 (19th November 2009) - Arriola, L; Martinez-Camblor, P; Larrañaga, N; Basterretxea, M; Amiano, P; Moreno-Iribas, C; Carracedo, R; Agudo, A; Ardanaz, E; Barricarte, A; Buckland, G; Cirera, Lluis; et al.
Abstract : Background: The association between alcohol consumption and coronary heart disease (CHD) has been widely studied. Most of these studies have concluded that moderate alcohol intake reduces the risk of CHD. There are numerous discussions regarding whether this association is causal or biased. The objective of this paper is to analyse the association between alcohol intake and CHD risk in the Spanish cohort of the European Prospective Investigation into Cancer (EPIC). Methods: Participants from the EPIC Spanish cohort were included (15 630 men and 25 808 women). The median follow-up period was 10 years. Ethanol intake was calculated using a validated dietary history questionnaire. Participants with a definite CHD event were considered cases. A Cox regression model adjusted for relevant co-variables and stratified by age was produced. Separate models were carried out for men and women. Results: The crude CHD incidence rate was 300.6/100 000 person-years for men and 47.9/100 000 person-years for women. Moderate, high and very high consumption was associated with a reduced risk of CHD in men: hazard ratio 0.90 (95% CI 0.56 to 1.44) for former drinkers, 0.65 (95% CI 0.41 to 1.04) for low, 0.49 (95% CI 0.32 to 0.76) for moderate, 0.46 (95% CI 0.30 to 0.71) for high and 0.50 (95% CI 0.29 to 0.85) for very high consumers. A negative association was found in women, with p values above 0.05 in all categories. Conclusions: Alcohol intake in men aged 29–69 years was associated with a more than 30% lower CHD incidence. This study is based on a large prospective cohort study and is free of the abstainer error.